Znaczenie szkół katolickich dla formacji katolików w Anglii i Walii - Osewska, Elżbieta (Studia Pastoralne, 2026)
In order to present the meaning of Catholic schools in the formation of Catholics in England and Wales, the author explores the social, religious and educational context of the past decades in England and Wales. Due to a high level of migration to the UK, with many ethnic groups coming from Asia, Africa and Latin America, the British society has been affected and transformed profoundly by the variety of cultures, religions, traditions and habits, proper to the migrating communities. This historical migration started a complex process of a global transformation of the society, which made it impossible for institutional religions to maintain their position and role as in the past. The Catholic population in England and Wales nowadays is composed of people of ethnic English descent, people of Irish origins, converts or the descendants of converts from Anglicanism or other Protestant denominations, and lately, Catholics from Catholic countries – mainly Poland. The present composition of the Catholic Church is thus highly diversified, and culturally heterogeneous. Nevertheless, Catholic schools in England and Wales have played an important role in searching for an interpretation of the emerging authentic forms of Christian faith and forming Catholics who are ready to see God’s presence within their experience and continually renew their daily lives in the light of the Gospel.